Test of liquid metal lithium capillary-porous system with stationary plasma in PLM device. (December 2020) - Budaev, V.P.; Fedorovich, S.D.; Lublinsky, I.E.; Vertkov, A.V.; Karpov, A.V.; Gubkin, M.K.; Van Oost, G.; Martynenko, Yu.V.; Frick, P.G.; Sviridov, E.V.; Gerasimov, D.N.; Lubenchenko, A.V.; et al.
Abstract: Lithium capillary-porous system (CPS) as a mat between molybdenum grids fixed in a molybdenum module was tested in PLM plasma device for 3 hours in a steady state helium discharge with plasma parameters relevant to scrape-off-layer and divertor plasma of large tokamak. The plasma load on the CPS was of 1 MW / m 2 led to surface heating up to 700 °C and vaporization of lithium to plasma. Lithium ions was registered by optical emission spectra from plasma. The redeposition of vaporized lithium was detected on the PLM in-vessel components. Inspections of CPS modules after plasma irradiation did not reveal any damage of molybdenum grids.